Comparative Characteristics of Shoulder Blade (Scapula) of Kashmir Stag (Cervuscanadensishangul), Common Leopard (Panther pardus), Himalayan Goral (Nemorhaedus goral), Spotted Deer (Axis axis) and Himalayan Bear (Ursusthibetanus) - Firdous Ahmad,; Umar Nazir,; Rashid Yahya, (Indian Journal of Veterinary Anatomy, 2025)
A comparative study was conducted on the scapula of the Kashmir Stag (Cervuscanadensishangul), Common Leopard (Panther pardus), Himalayan Goral (Nemorhaedus goral), Spotted Deer (Axis axis), and Himalayan Bear (Ursusthibetanus). The study included morphological and certain morphometrical parameters of the scapula bones of these animals. In Kashmir Stag, Himalayan Goral, and Spotted Deer the bone was triangular with a spine that divides the lateral surface into two unequal halves. In Himalayan Bear, the scapula was rectangular in outline, extremely wide, and very well-presented supraspinatus and infraspinatus fossae. In Common Leopard, the scapula was a quadrilateral flat bone, thespine was inclined to the infraspinous fossa, and it was not tuberous in the middle. A well-developed suprahamate process was present before the acromion process over the infraspinous fossa in the scapulae of the Common Leopard and in Himalayan Bear. The features can be used to identify the animal species and serve as a forensic tool.